EFFECT OF BOARD STRUCTURE ON CORPORATE SOCIAL AND ENVIRONMENTAL SUSTAINABILITY PERFORMANCE OF LISTED NIGERIAN OIL AND GAS FIRMS - Motunrayo Elizabeth OMOLEHIN; Folashade Olufunke OBAJE (Malete Journal of Accounting and Finance, 2024)
Empirical review has established a paucity of research around board structure and sustainability performance, especially in Nigeria. This study, therefore, explored grey areas in the literature regarding board structure and sustainability performance. The panel data generalized least squares (random effect) method was used to analyse data sourced from annual reports, sustainability reports of selected oil and gas firms listed on the floor of the Nigeria Exchange from 2012 to 2022 and CSRHub database. The results revealed that board independence and board gender diversity positively but insignificantly affect social performance; meanwhile, board sustainability committee and board nationality diversity positively and significantly affect social performance. Also, the study found that Board independence positively and insignificantly affect environmental performance; meanwhile, board gender diversity, board nationality diversity and board sustainability committee positively and significantly affect environmental performance. This study recommends that oil and gas firms adopt the principles of increasing independence, increasing gender and nationality diversity, and incorporating sustainability committees to improve social and environmental sustainability performance